2019
DOI: 10.1080/02650487.2019.1607450
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical side effects of green advertising: how purchasing green products may instigate licensing effects for consumers with a weak environmental identity

Abstract: (2019) Paradoxical side effects of green advertising: how purchasing green products may instigate licensing effects for consumers with a weak environmental identity,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 73 publications
(118 reference statements)
1
29
0
Order By: Relevance
“…Overall, females seemed to be more responsive to green appeals, and health appeal was found to be consistently the most important appeal regardless of age and gender. The differences in the effects of green appeals versus non-green appeals have been another research stream with limited studies (Kong & Zhang, 2013; Meijers, Noordewier, Verlegh, Willems, & Smit, 2019; Schuhwerk & Lefkoff-Hagius, 1995). The majority of the articles indicated that green appeals led to more favorable ad attitudes, brand attitudes, and PI than non-green ones (Bailey et al, 2018; Bickart & Ruth, 2012; Grimmer & Woolley, 2014; Kong & Zhang, 2014; Schuhwerk & Lefkoff-Hagius, 1995; Xue & Muralidharan, 2015).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…Overall, females seemed to be more responsive to green appeals, and health appeal was found to be consistently the most important appeal regardless of age and gender. The differences in the effects of green appeals versus non-green appeals have been another research stream with limited studies (Kong & Zhang, 2013; Meijers, Noordewier, Verlegh, Willems, & Smit, 2019; Schuhwerk & Lefkoff-Hagius, 1995). The majority of the articles indicated that green appeals led to more favorable ad attitudes, brand attitudes, and PI than non-green ones (Bailey et al, 2018; Bickart & Ruth, 2012; Grimmer & Woolley, 2014; Kong & Zhang, 2014; Schuhwerk & Lefkoff-Hagius, 1995; Xue & Muralidharan, 2015).…”
Section: Literature Review and Theoretical Foundationmentioning
confidence: 99%
“…There is ample support from literature that self-identity typically influences behavior (e.g., Biddle, Bank, and Slavings 1987; Grewal, Mehta, and Kardes 2000; Cook, Kerr, and Moore 2002; Stets and Biga 2003; Dermody et al. 2018; Meijers et al. 2019).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…More formally: Hypothesis 3: Perceived consumer effectiveness mediates the relationships between the type of CSR communication and (a) the attitude toward hotels’ CSR communication, as well as (b) the intention to behave unethically.As a large part of CSR pertains to sustainability efforts, we further expect that individuals’ pro-environmental identity will influence their attitude toward hotels’ CSR communication and intention to behave unethically while on holiday. Self-identity refers to how individuals see themselves and the labels they use to describe themselves, in relation to particular behaviors (Meijers et al. 2019).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations